Posterior Reversible Encephalopathy Syndrome in a Pediatric Patient with End-Stage Renal Disease - Ionela-Loredana Popa; Mihaela Bălgrădean; Mariana Costin; Anca Bobircă; Cristina Bologa; Teodora Armășelu; Florin Bobircă; Anca Croitoru (Children, 2023)
Posterior reversible encephalopathy syndrome (PRES) is a clinical and neuroimaging syndrome that can affect both children and adults and has variable etiology. It is clinically defined by headaches, consciousness disorders, seizures and visual disturbances. Early recognition (clinical and imaging) can lead to appropriate general measures to correct the underlying cause of PRES. In this paper, we report a case of PRES in an eight-year-old boy with bilateral renal hypoplasia and end-stage renal disease (ESRD).